Análise de flares estelares usando as cores do CoRoT - Márcia Cristina de Freitas (2020)
In this work, more than 20 stars observed by the color channels of the CoRoT satellite that present flare emissions and whose spectral type was determined spectroscopically were analyzed. Most of the analyzed stars have a clear periodic modulation in their light curve and we identified that they usually have an excess emission in the red channel in relation to the blue one during periods of minimum flux, indicating the presence of a cold spot on their surface. Also, more than 300 flares were identified and analyzed, and their profile in the light curve were fitted. We observed that flares emit, on average, three times more in the blue channel than in the red channel. As with solar flares, we did not find a relationship between the amplitude and duration of the flares. The classic profile of a flare shows that the rising phase (that is, the increase in brightness until reaching its maximum) is shorter than the descending phase (the decrease in brightness after its maximum). In fact, 81% of the flares analyzed in solitary stars show this behavior. On the other hand, we find that only 56 % follow the classic profile in binary stars. Flares that have a higher rise time than its decay time also have a smaller total duration and larger impulsivity. Furthermore, it was found that, in about 55% of the flares, the maximum peak occurs first in the blue channel when compared to the red one. This study makes an important contribution to the effor of understanding the physical processes involved in stellar flares, which also leads to understanding the flares in the Sun.